ANALISIS YURIDIS SECURITIES CROWD FUNDING DALAM PERSPEKTIF UNDANG-UNDANG PENANAMAN MODAL DAN UNDANG-UNDANG PASAR MODAL - Fajrina, Yuni; Wibisono, Arief; Kusnowibowo, Ahmad Saleh (Jurnal Ilmiah Global Education, 2023)
Technology-based fundraising or crowdfunding has become a popular trend in corporate funding thanks to the development of the internet. This research uses a normative juridical method by examining library materials to analyze legal protection in crowdfunding services based on the Investment Law and the Capital Market Law. The results showed that legal protection of crowdfunding activities has not been maximized. There is legal uncertainty regarding OJK regulations that are responsible for losses due to third party errors. There needs to be more detailed rules regarding liability in this case. In addition, the current legal structure in the crowdfunding activity platform is considered not clear enough in risk reduction and loss prevention for users. The lack of information due to the low level of knowledge of the Indonesian people about crowdfunding is also a challenge in efforts to protect actors and users from the risks of this activity. Nevertheless, crowdfunding activities have great potential in improving the Indonesian economy after the recession due to the Covid-19 pandemic